PENGARUH METODE LATIHAN FLEKSIBILITAS TERHADAP KEMAMPUAN TENDANGAN DASAR PADA ATLET PEMULA ALAM BARAJO TAEKWONDO ACADEMY JAMBI - Arnot Daniel Panggabean; Boy Indrayana; Ahmad Muzzafar (PT. Hasba Edukasi Mandiri, 2025)
This study aims to explore the role of communication technology in enhancing the effectiveness of learning media in distance education, specifically through the LMS Damel utilized by UIN Siber Syekh Nurjati Cirebon. The study employs a qualitative descriptive approach using interviews, observations, and documentation as methods for data collection. Findings indicate that LMS Damel effectively improves academic interaction, accessibility of learning materials, and the management of educational evaluation. Identified challenges include the quality of internet connectivity, limited technological resources, and varying student motivation in participating in online learning.